Entrance to the northern shrine in the Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
View of the entrance to the northern shrine in the Neelkanth Mahadev Temple. Both the north and south shrines have identical dvarashakhas (door jambs) except for the deity couple above the lintel beam supported on the pillars of the shrine. The shrine has a depiction of Vishnu Lakshmi seated on Garuda. The lintel with the Vishnu Lakshmi sculpture has deep niches like the ones that are found on the exterior walls of temples.